Španska gripa 1918-1919 - aspekti demografskih implikacija - Beštić-Bronza, Slavojka (Scripta Medica, 2020)
The usual perception of inﬂuenza pandemic that ravaged throughout 1918–19 (and in much less manner also in 1920) is structured into analyzing of three different waves that stroke almost whole of humanity in quick succession from spring 1918 onwards. Results of the pandemics regarding the recorded statistics of inﬂuenza morbidity and mortality are in the focus of medical science for long time. Although evolution of estimations throughout last several decades almost always tended towards higher and higher estimations, which led to visions of over 100 million deaths throughout definitely most deadly influenza epidemic, it is clear that such numbers should be taken with huge dose of skepticism. Approach of the paper will be centered around methods for demographic estimations and especially evaluations of historical development in the situation where influenza pandemic overlapped with World War I.